Influence of clinically differentiated estrus vaginal pH windows on offspring sex ratio following artificial insemination in west African dwarf goats - Oluropo Michael Obafemi; Ajibola Olaotan Obafemi; Afolarin Bolaji; Oluwadamilare Olufisayo Leigh (Ovozoa: Journal of Animal Reproduction, 2026)
The offspring sex ratio in mammals is generally considered to occur by chance, with many reports indicating an approximately 1:1 (male:female) ratio. The ability to influence this natural biological ratio could provide significant socioeconomic benefits in livestock production. Although sex-sorted semen offers a means of predetermining offspring sex, its high cost and reduced fertility following processing limit its accessibility to many livestock farmers in developing countries. Therefore, identifying a simpler and more affordable alternative would be highly beneficial. A total number of twenty-one goats were used for this experiment, comprising one Boer buck and 20 West African Dwarf (WAD) goat does weigh between 25 and 35 kg.  Estrus was synchronized using two intramuscular injections of 250 µg Synchromate® administered 11 days apart. Semen was collected from the buck using an electroejaculator (EE) after restraint, evaluated, and extended with a standard egg yolk sodium citrate extender. Each doe was artificially inseminated twice. Before each insemination vaginal pH was measured using a digital pH meter and recorded. Based on the vaginal pH at insemination, seven does were inseminated under acidic conditions, four under neutral conditions, and nine under alkaline conditions. All twenty (20) inseminated does gave birth to a total of 33 kids, comprising 15 females and 18 males. Further studies are needed to investigate the mechanisms responsible for changes in vaginal pH during estrus and to determine whether manipulation of vaginal pH could provide a practical approach to influencing offspring sex ratio in goats.